Legal Protection for People with Disabilities in Indonesia in the Perspective of Justice Theory - Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini; I Wayan Lasmawan (Unnes Law Journal, 2022)
Respect, protection and fulfillment of the rights of persons with disabilities are the obligations of the state. This is also confirmed in Law Number 39 of 1999 concerning Human Rights, so that society has the responsibility to respect the rights of Persons with Disabilities. During this time, Persons with Disabilities have experienced a lot of discrimination which results in not fulfilling the implementation of the rights of persons with disabilities. The passing of Law Number 19 of 2011 concerning the Ratification of the Convention on the Rights of Persons with Disabilities on November 10, 2011, showed that the commitment and seriousness of the Indonesian Government to respect, protect and fulfill the rights of persons with disabilities which in turn are expected to improve the welfare of persons with disabilities. This study confirmed and highlighted that legal protection for people with disabilities has been provided in several laws and regulation both national and international legal system. The implementation and fulfillment of the rights of persons with disabilities is aimed at realizing a higher quality, fairer, physically and mentally prosperous, and dignified standard of life for persons with disabilities. In addition, the implementation and fulfillment of rights are also aimed at protecting persons with disabilities from neglect and exploitation, harassment and all discriminatory acts, as well as human rights violations.